Fenomen belorusko-poljske literarne meje - Khmialnitski, Mikalai (Slavia Centralis, 2021)
The article discusses the phenomenon of the Belarusian-Polish literary borderland and reveals its historical, social and cultural components, unveiling its national characteristics. The role of the ethnic factor, folklore elements and autobiographical discourse in the borderland literature is described. The national identity problem of writers born in the borderland receives special attention. The extent to which the problem has been researched is analysed within the scope of the literature studies of Poland and Belarus.
Keywords: literary borderland; discourse analysis; imagology; literary process; identity; Polish Belarusian connections